2024
DOI: 10.1097/mco.0000000000001028
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and its impact on fetal and neonatal brain development: current opinion in pediatrics

Nina M. Frerichs,
Tim G.J. de Meij,
Hendrik J. Niemarkt

Abstract: Purpose of review Emerging evidence suggests that the gut microbiota and its metabolites regulate neurodevelopment and cognitive functioning via a bi-directional communication system known as the microbiota-gut-brain axis (MGBA). Recent findings The MGBA influences brain development and function via the hypothalamic-pituitary axis, the vagal nerve, immune signaling, bacterial production of neurotransmitters, and microbial metabolites like short-chain fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…SCFAs have been shown to influence gap junction gating in the gut and blood–brain barrier integrity, contributing to brain homeostasis, modulating neuroinflammation, and stimulating brain-derived neurotrophic factor (BDNF) expression. Yang et al (2019) showed that SCFA treatment of human neural progenitor cells at physiological levels influenced the expression of the neurogenesis, proliferation, and apoptosis-related genes ATR, BCL2, BID, CASP8, CKD2, E2F1, FAS, NDN, and VEGFA ( Agnihotri and Moharjeri, 2022 ; Frerichs et al, 2024 ). BDNF is a crucial neurotrophin for neuronal differentiation, plasticity, and the establishment of synaptogenesis ( Rodolaki et al, 2023 ).…”
Section: Gdm and Its Effects On Fetal Neurodevelopmentmentioning
confidence: 99%
“…SCFAs have been shown to influence gap junction gating in the gut and blood–brain barrier integrity, contributing to brain homeostasis, modulating neuroinflammation, and stimulating brain-derived neurotrophic factor (BDNF) expression. Yang et al (2019) showed that SCFA treatment of human neural progenitor cells at physiological levels influenced the expression of the neurogenesis, proliferation, and apoptosis-related genes ATR, BCL2, BID, CASP8, CKD2, E2F1, FAS, NDN, and VEGFA ( Agnihotri and Moharjeri, 2022 ; Frerichs et al, 2024 ). BDNF is a crucial neurotrophin for neuronal differentiation, plasticity, and the establishment of synaptogenesis ( Rodolaki et al, 2023 ).…”
Section: Gdm and Its Effects On Fetal Neurodevelopmentmentioning
confidence: 99%